Recent developments in electrochemistry at the interface between two immiscible electrolyte solutions for ion sensing1. Issue 12 (21st June 2015) - Herzog, Grégoire
<x xml:space="preserve">Abstract</x> The most recent developments on electrochemical sensing of ions at the liquid–liquid interface are reviewed here.